2018
DOI: 10.18805/ijar.b-3427
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasitic infections in cattle and swamp buffalo of Guwahati, Assam, India

Abstract: The objective of the present study was to determine the prevalence of gastrointestinal (G.I.) parasitic infections in cattle and swamp buffalo of Assam, India. A total of 3597 fecal samples of cattle (2339)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 124 publications
4
11
0
Order By: Relevance
“…Haemonchus, Oesophagostomum, Cooperia, Bunostomum and Mecistocirrus are the most important genera prevalent in cattle of North-eastern India (Latha et al, 2013;Das et al, 2015) including other parts of the country (Bulbul et al, 2014;Allaie et al, 2018) like our observations in the present study.…”
Section: Strongyloides Trichostrongylussupporting
confidence: 86%
“…Haemonchus, Oesophagostomum, Cooperia, Bunostomum and Mecistocirrus are the most important genera prevalent in cattle of North-eastern India (Latha et al, 2013;Das et al, 2015) including other parts of the country (Bulbul et al, 2014;Allaie et al, 2018) like our observations in the present study.…”
Section: Strongyloides Trichostrongylussupporting
confidence: 86%
“…Our result almost correlates with the ndings of (Achhami, Sharma, & Bam, 2016) in musk deer of Langtang National Park Nepal. Das et al, (2018) Richards et al, (1995) reported intestinal roundworms and ukes in the red fox(Vulpes vulpes), and (Grzegorz, Michal, Leszek, Wojciech, & Krzysztof, 1999) reported Babesia nicroti in rodents like Microtus oeconomus & Microtus agrestis . Interspecies transmission of parasites takes place due to the interaction of animals in a common environment (Bengis, Kock, & Fischer, 2002 Around 90 % of carnivores, 77 % of livestock, and 60% of human pathogens are multi-host in nature and among the 77% of livestock pathogens, most of them have the capacity of affecting wild ungulates (Cleave land, Laurenson, & Taylor, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The commonly reported parasites in buffaloes include strongyles (Karim et al, 2016;Nurhidayah et al, 2019), Trichuris sp., Moniezia sp., Toxocara vitulorum (Dorny et al, 2015;Gunathilaka et al, 2018), and Theileria sp. (Rohaya et al, 2017); as well as trematodes such as Fasciola gigantica (Das et al, 2018;Zhang et al, 2019), Paramphistomes (Gunathilaka et al, 2018) and Gigantocotyle explanandum (Malik et al, 2017). The…”
Section: Introductionmentioning
confidence: 99%